Fatigue behavior of planar CH3NH3PbI3 perovskite solar cells revealed by light on/off diurnal cycling. (September 2016) - Huang, Fuzhi; Jiang, Liangcong; Pascoe, Alexander R.; Yan, Yanfa; Bach, Udo; Spiccia, Leone; Cheng, Yi-Bing
Abstract: Long-term stability represents a major challenge for the commercial deployment of hybrid perovskite solar cells (PSCs). The stability of solar cells is commonly tested under continuous illumination over extended periods of time, for example, 1000 h. We have found that such a method does not adequately reflect the long-term performance of perovskite solar cells under the diurnal solar irradiation cycles experienced in real-world applications. We report a new characterization protocol of multiple 12-h cycles of darkness and illumination, uncovering a unique 'fatigue' behavior of PSCs. The PSC efficiency was found to decrease to 50% or less of its maximum value after storage in the dark for 12 h under open circuit conditions. The solar cell performance was capable of recovering to its maximum value in the subsequent 12-h illumination period, but the recovery rate slowed significantly with successive illumination/darkness cycles. This fatigue mechanism was strongly dependent on the cell temperature. The identification of this fatigue behavior renders our proposed characterization protocol an essential component of perovskite solar cell testing. Highlights: Perovskite solar cells (PSC) were tested in multiple 12-h cycles of darkness and illumination. The illumination/darkness cyclic tests uncovered a unique 'fatigue' behavior of PSCs. This fatigue mechanism was strongly dependent on the cell temperature. A new characterization protocol is proposed as an essential component of perovskite solar cell testing.